2017
DOI: 10.4103/jomfp.jomfp_241_16
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between histological differentiation and disease recurrence of primary oral squamous cell carcinoma

Abstract: Background:Although advance techniques were available for diagnosis and prognosis of oral cancer, histopathology was used as major method in clinical routine. Of all oral subsites, buccal mucosa squamous cell carcinoma is aggressive in nature with poor survival. Therefore, the aim of the present study was to evaluate the relation of tumor histopathological grade with disease recurrence of buccal squamous cell mucosa carcinoma.Materials and Methods:A retrospective study was carried out in regional cancer resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 13 publications
4
30
0
Order By: Relevance
“…The mutations of KMT2D and TERT have been reported to be associated with prognosis in different tumors (57)(58)(59). Histopathological grade is considered to be associated with the clinical characteristics of lymphovascular invasion, perineural invasion, tumor differentiation, lymph node and metastasis, as well as the prediction of prognosis (60,61). In the present study, the mutations of STK11, GNAS, KMT2D, MAGI2 and TERT were mainly detected in poorly differentiated CCA, indicating that these genes might be potential biomarkers to predict the differentiation of CCA tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The mutations of KMT2D and TERT have been reported to be associated with prognosis in different tumors (57)(58)(59). Histopathological grade is considered to be associated with the clinical characteristics of lymphovascular invasion, perineural invasion, tumor differentiation, lymph node and metastasis, as well as the prediction of prognosis (60,61). In the present study, the mutations of STK11, GNAS, KMT2D, MAGI2 and TERT were mainly detected in poorly differentiated CCA, indicating that these genes might be potential biomarkers to predict the differentiation of CCA tumors.…”
Section: Discussionmentioning
confidence: 99%
“…There were 26 studies originated from Asian countries (China, India, Korea, Japan, and Pakistan), and the remaining ten studies were from non-Asian countries (USA, Europe, Australia, Italy and Brazil). Among them, ten studies included oral tongue SCC [14][15][16][17][18][19][20][21][22][23][24] , and the other two studies were focused on floor of mouth cancer 7 and buccal mucosa SCC 25 , respectively. The tumor site of OSCC was mixed in the other 24 studies .…”
Section: Study Characteristics Of Included Studiesmentioning
confidence: 99%
“…OS, DSS, DFS were the identified endpoints. Among them, 11 studies including 12783 patients reported the OS 7,17,20,22,26,30,31,37,38,41,46 (Figure 3A), seven studies involving 3470 patients reported the DSS 24, 32, 37-39, 46, 47 (Figure 3B), and the other three researches with 731 follow-ups reported the DFS 25,30,43 ( Figure 3C). Among studies focused on OS, Wei study (2019) 46 from Group DSS was excluded on account of overlapping with the patient pool of Chen study (2014) 31 .…”
Section: Prognostic Value Of LVI In Osccmentioning
confidence: 99%
“…Keratins (KRTs) are important differentiation markers both in normal, keratinized and neoplastic oral squamous cell carcinoma (OSCC). So, the WHO has categorized OSCC into four grades: Grade I (well-differentiated; > 50% cellular keratinizaion-K4), Grade II (moderately differentiated; 20-50% keratinization-K3), Grade III (poorly differentiated; 5-20% keratinization-K2) and Grade IV (undifferentiated; 0-5% keratinization-K0-K1) [1].…”
Section: Introductionmentioning
confidence: 99%
“…These approaches are unable to provide full-length (FL) transcript sequences, which required to identifying novel tumor-specific isoforms and fusion genes. Various studies have been reported the involvement of tumor-specific isoforms and fusion gens in pathogenesis and progression of cancer [ 1 , 9 12 ]. Furthermore, studies suggest that the epidermal growth factor receptor (EGFR) may be a promising target for therapy of OSCC and EGFR overexpression is associated with worse prognosis of the disease [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%